Mutagenic, Genotoxic and Immunomodulatory effects of Hydroxychloroquine and Chloroquine: a review to evaluate its potential to use as a prophylactic drug against COVID-19 - Allan Giri; Ankita Das; Ajoy K. Sarkar; Ashok K. Giri (Genes and Environment, 2020)
Abstract Hydroxychloroquine (HCQ) and Chloroquine (CQ) are two anti-malarial drugs that are now being extensively used by front-line healthcare workers and other common people as a prophylactic drug against the Corona Virus Disease − 19 (COVID-19) in India and as well as in many parts of the world. While only a few in vitro studies have pointed to some efficacy of these drugs as a prophylactic against COVID-19, to date, there are no clinical studies that have established any clinical efficacy of these drugs as a prophylactic. These drugs are commonly used for the treatment of Rheumatoid Arthritis (RA) and Systemic Lupus Erythematosus (SLE) because of its immunomodulatory effects. Previously, we have evaluated the genetic toxicology of different drugs and chemicals including antimalarial drug CQ both in vitro and in vivo. Thus, we recognize the need to critically review the mutagenic, genotoxic, and immunomodulatory effects of these drugs, to find out whether it is safe to use as a prophylactic drug against COVID-19. Existing literature suggests that CQ can induce mutagenic and genotoxic effects in multiple test systems and both the drugs have immunomodulatory effects. There was no data available to evaluate the mutagenicity and genotoxicity for HCQ. However, during metabolism about 60% of both the drugs remain unchanged and about 40% of the drugs are metabolized into two metabolites, desethylchloroquine and bisdesethylchloroquine by the action of the cytochrome P450 (CYP) enzymes in the liver. Both HCQ and CQ are immunomodulatory drugs and have the potential to suppress normal immune system activation. In this review, we have elucidated the mechanism of immunomodulation by both HCQ and CQ and highlighted the mutagenic and genotoxic effects from the available literature. This article is written with the sole objective that the reader will be able to recognize the adverse effects of these drugs when consumed by healthy individuals as a prophylactic. Current literature indicates that healthy individuals should refrain from the use of these drugs until further investigation.